Meridional Gulf Stream Shifts Can Influence Wintertime Variability in the North Atlantic Storm Track and Greenland Blocking - Terrence M. Joyce; Young‐Oh Kwon; Hyodae Seo; Caroline C. Ummenhofer (Geophysical Research Letters)
Abstract After leaving the U.S. East Coast, the northward flowing Gulf Stream (GS) becomes a zonal jet and carries along its frontal characteristics of strong flow and sea surface temperature gradients into the North Atlantic at midlatitudes. The separation location where it leaves the coast is also an anchor point for the wintertime synoptic storm track across North America to continue to develop and head across the ocean. We examine the meridional variability of the separated GS path on interannual to decadal time scales as an agent for similar changes in the storm track and blocking variability at midtroposphere from 1979 to 2012. We find that periods of northerly (southerly) GS path are associated with increased (suppressed) excursions of the synoptic storm track to the northeast over the Labrador Sea and reduced (enhanced) Greenland blocking. In both instances, GS shifts lead those in the midtroposphere by a few months.